Implementasi Pendidikan Multikultural di SD Negeri Empang Bahagia 3 Kota Tangerang - Magdalena, Ina; Uthantry, Zuanita Hershifani; Marctines, Gabriella Sinthia (TSAQOFAH, 2023)
Multicultural education has historically recognized cultural diversity, ethnicity, religion, race, and they come with their own identities. The most important thing in multicultural education is that an educator must master and teach subjects and instill core values such as democracy. humanism, and pluralism as well as an appreciation of inclusive diversity in students. This research discusses multicultural education for children at SD Negeri Empang Bahagia 3 Kota Tangerang in situations where differences in culture, religion, race, ethnicity and others can have a negative impact on the interactions of Indonesian society. This research is a qualitative research that includes field research. The results of this study are four themes that describe how teachers develop and prepare strategies for learning multiculturalism.